2018
DOI: 10.1186/s13018-018-0913-z
|View full text |Cite
|
Sign up to set email alerts
|

The etiology of idiopathic congenital talipes equinovarus: a systematic review

Abstract: BackgroundAlso known as clubfoot, idiopathic congenital talipes equinovarus (ICTEV) is the most common pediatric deformity and occurs in 1 in every 1000 live births. Even though it has been widely researched, the etiology of ICTEV remains poorly understood and is often described as being based on a multifactorial genesis. Genetic and environmental factors seem to have a major role in the development of this disease. Thus, the aim of this review is to analyze the available literature to document the current evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
81
1
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 67 publications
1
81
1
9
Order By: Relevance
“…It has higher recurrence within families; however, a twin study suggested that environmental factors also play a significant role in the etiology of congenital clubfoot (Engell et al, ). Several environmental risk factors, in particular maternal smoking, have been related to the risk of congenital clubfoot (Pavone et al, ; Werler et al, ). Some maternal medical conditions and medication use could increase the risk of congenital clubfoot, such as obesity (Werler et al, ) and use of selective serotonin reuptake inhibitors (SSRI) (Wemakor et al, ; Yazdy, Mitchell, Louik, & Werler, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has higher recurrence within families; however, a twin study suggested that environmental factors also play a significant role in the etiology of congenital clubfoot (Engell et al, ). Several environmental risk factors, in particular maternal smoking, have been related to the risk of congenital clubfoot (Pavone et al, ; Werler et al, ). Some maternal medical conditions and medication use could increase the risk of congenital clubfoot, such as obesity (Werler et al, ) and use of selective serotonin reuptake inhibitors (SSRI) (Wemakor et al, ; Yazdy, Mitchell, Louik, & Werler, ).…”
Section: Introductionmentioning
confidence: 99%
“…Idiopathic pes equinovarus (clubfoot) belongs to a group of fibroproliferative disorders involving the musculoskeletal system and its origin remains unknown. This defect occurs approximately once per 1000 births . The guideline on the diagnosis and treatment of this disease was recently published by Besselaar et al These methods, although successful, are of a long‐term nature and very demanding for the child patients and their parents alike because a number of plasters need to be applied starting at a very young age.…”
mentioning
confidence: 99%
“…However, in 80% of cases, this occurs separately or as an idiopathy. Genetic and environmental components are believed to be involved (Gibbons & Gray, 2013;Pavone et al, 2018).…”
Section: Discussionmentioning
confidence: 99%